Gallium selenide clusters generated via laser desorption ionisation quadrupole ion trap time-of-flight mass spectrometry - Pečinka, Lukáš; Prokeš, Lubomír; Havel, Josef (Rapid communications in mass spectrometry, 2019)
RATIONALE: Gallium selenide thin films important for electronics and phase-change materials are prepared via pulsed laser deposition (PLD); however, there are no studies concerning the analysis of gallium selenide clusters formed in the gas phase. Laser desorption ionisation (LDI) combined with time-of-flight mass spectrometry (TOF-MS) has great potential to generate charged Gam Sen clusters, to analyse them and thus to develop new materials. METHODS: LDI of Ga-Se mixtures using a pulsed laser (337 nm nitrogen) was used to generate gallium-selenide clusters. Mass spectra were recorded (in positive and negative ion mode) on a TOF mass spectrometer equipped with a quadrupole ion trap and reflectron mass analyser. RESULTS: Ga-Se mixtures were found to be suitable for laser ablation synthesis (LAS) of gallium selenide clusters, although their composition was strongly dependent on the laser energy. The effect of laser energy on the stoichiometry of the generated clusters was established. In total, over 100 gallium selenide Gam Sen clusters were generated and identified from Ga-Se mixtures. LDI of Ga2 Se3 crystals showed almost the same clusters up to m/z 1000 with lower intensities, whereas no clusters from Ga2 Se3 were observed above m/z 1000. CONCLUSIONS: A family of over 100 gallium selenide clusters, generated and identified for the first time, shows rich and complex chemistry. Some of the clusters represent new compounds that have the potential to be used in the development of advanced materials.